Abolishment of morphology-based taxa and change to binomial species names: 2022 taxonomy update of the ICTV bacterial viruses subcommittee - Dann Turner; Andrey N. Shkoporov; Cédric Lood; Andrew D. Millard; Bas E. Dutilh; Poliane Alfenas-Zerbini; Leonardo J. van Zyl; Ramy K. Aziz; Hanna M. Oksanen; Minna M. Poranen; Andrew M. Kropinski; Jakub Barylski; et al. (Archives of Virology, 2023)
This article summarises the activities of the Bacterial Viruses Subcommittee of the International Committee on Taxonomy of Viruses for the period of March 2021−March 2022. We provide an overview of the new taxa proposed in 2021, approved by the Executive Committee, and ratified by vote in 2022. Significant changes to the taxonomy of bacterial viruses were introduced: the paraphyletic morphological families Podoviridae , Siphoviridae , and Myoviridae as well as the order Caudovirales were abolished, and a binomial system of nomenclature for species was established. In addition, one order, 22 families, 30 subfamilies, 321 genera, and 862 species were newly created, promoted, or moved.